Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/jhep01(2014)123
|View full text |Cite
|
Sign up to set email alerts
|

Muon g − 2 vs LHC in supersymmetric models

Abstract: There is more than 3σ deviation between the experimental and theoretical results of the muon g − 2. When interpreted in SUSY extensions of the SM, this anomaly suggests that some of the SUSY particles have a mass of order 100 GeV. We study searches for those particles at the LHC with particular attention to the muon g − 2. In particular, the recent results on the searches for the non-colored SUSY particles are investigated in the parameter region where the muon g − 2 is explained. The analysis is independent o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 72 publications
3
85
0
Order By: Relevance
“…The points are similar to the scenarios studied in Ref. [20], where it was also shown that such parameter choices, together with the squark masses defined below, are compatible with current LHC data. We use a notation similar to Ref.…”
Section: Overview Of Susy Contributions To a µsupporting
confidence: 70%
See 1 more Smart Citation
“…The points are similar to the scenarios studied in Ref. [20], where it was also shown that such parameter choices, together with the squark masses defined below, are compatible with current LHC data. We use a notation similar to Ref.…”
Section: Overview Of Susy Contributions To a µsupporting
confidence: 70%
“…Many recently proposed models which stay within the MSSM framework involve rather split spectra, e.g. heavy coloured, light non-coloured SUSY particles [20][21][22][23], heavy third family, lighter first and second family [24], non-universal gaugino masses [25,26], large Higgsino masses and large stop mixing from more generic gauge mediation [27].…”
Section: Introductionmentioning
confidence: 99%
“…(3.12) because µ is large. This is connected with the larger contribution from the neutralino-smuon part of the diagrams for a SUSY µ [129][130][131]. The contributions from the above type of diagram is more dominant for tan β = 20 where µ is much larger than the case of tan β = 40.…”
Section: Muon G −mentioning
confidence: 83%
“…The point for tan β = 20 in Region-I corresponding to smaller µ satisfies a SUSY µ constraint of eq. (3.12) principally because of smaller lighter chargino mass [129][130][131]. For the Region -I point corresponding to tan β = 40, there is a natural enhancement of a SUSY µ due to larger tan β.…”
Section: Muon G −mentioning
confidence: 99%
See 1 more Smart Citation